The well-grounded data analyst solve messy data problems like a pro - Asboth, David (Manning Publications, 2025)
The Well-Grounded Data Analyst introduces you to eight scenarios that every data analyst is bound to face. You'll practice author David Asboth's results-oriented approach as you model data by identifying customer records, navigate poorly-defined metrics, extract data from PDFs, and much more! It also teaches you how to take over incomplete projects and create rapid prototypes with real data. Along the way, you'll build an impressive portfolio of projects you can showcase at your next interview.
Online resource; title from title details screen (O'Reilly, viewed April 9, 2025)
Keywords: Research -- Vocational guidance; Data mining -- Vocational guidance; Business analysts -- Vocational guidance; Recherche; Orientation professionnelle; Exploration de données (Informatique); Orientation professionnelle; Analystes d'entreprise; Orientation professionnelle; Audiobooks; Livres audio